Simultaneous Bilateral Spontaneous Pneumothorax Revealed Birt-Hogg-Dubè Syndrome - Alessandro Tamburrini; Francesco Sellitri; Federico Tacconi; Francesco Brancati; Tommaso Claudio Mineo (Case Reports in Surgery)
Simultaneous bilateral spontaneous pneumothorax is a very rare clinical event, comprising approximately 1% of all spontaneous pneumothoraces. Clinical signs and symptoms may vary from mild chest pain and dyspnea to severe respiratory failure; nevertheless immediate treatment is mandatory as this condition can deteriorate and progress to tension pneumothorax. An underlying lung disease has been commonly described; in most istances primary or secondary tumors, interstitial diseases, and infectious diseases. Birt-Hogg-Dubè syndrome is a rare inherited disorder clinically characterized by multiple fibrofolliculomas, renal tumors, lung cysts, and, in ~24% of the patients, occurrence of spontaneous pneumothorax. In this case, we firstly report the concurrence of these rare conditions, as a patient presenting a simultaneous bilateral spontaneous pneumothorax was diagnosed with Birt-Hogg-Dubè syndrome based on the typical radiological findings and genetic testing of the folliculin gene located on chromosome 17.